An estimation of the optical constants of copper based on the FEFF 9 package: an update of previous results - Rivas Valles, Gildardo (2021)
The FEFF software package is based on a first-principles real space Green function (RSMS) scattering theory to calculate x-ray absorption fine-structure (XAFS) and forward scattering amplitudes (FSA). A procedure to obtain XAFS and FSA using FEFF version 9 is described and applied to crystalline metallic copper as an example. From this, an energy-dependent complex dielectric constant is calculated, from which other optical constants such as the complex index of refraction, absorption coefficient, reflectance, and energy-loss function are derived. The results are compared to values taken from the literature. It is found that they agree in the x-ray region; however, for photons corresponding to the ultraviolet (below 120 eV), the agreement is only qualitative.